2023
DOI: 10.3389/fnmol.2023.1215425
|View full text |Cite
|
Sign up to set email alerts
|

Brain cell type specific proteomics approach to discover pathological mechanisms in the childhood CNS disorder mucolipidosis type IV

Abstract: Mucolipidosis IV (MLIV) is an ultra-rare, recessively inherited lysosomal disorder resulting from inactivating mutations in MCOLN1, the gene encoding the lysosomal cation channel TRPML1. The disease primarily affects the central nervous system (CNS) and manifests in the first year with cognitive and motor developmental delay, followed by a gradual decline in neurological function across the second decade of life, blindness, and premature death in third or fourth decades. Brain pathology manifestations in MLIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…We have recently reported broad upregulation of lysosomal proteins as a hallmark of pathological molecular changes in the brain of Mcoln1 −/− mice. 29 A similar increase of lysosomal proteins was also reported in the single MLIV brain autopsy proteome, indicating the conservative nature of this phenomenon across species. 40 Additionally, the upregulation of lysosomal proteins was commonly reported in other lysosomal storage disorders, such as NPC, Gaucher, mucopolysaccharidoses, and others, and is thought to represent a compensatory mechanism for impaired lysosomal function.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…We have recently reported broad upregulation of lysosomal proteins as a hallmark of pathological molecular changes in the brain of Mcoln1 −/− mice. 29 A similar increase of lysosomal proteins was also reported in the single MLIV brain autopsy proteome, indicating the conservative nature of this phenomenon across species. 40 Additionally, the upregulation of lysosomal proteins was commonly reported in other lysosomal storage disorders, such as NPC, Gaucher, mucopolysaccharidoses, and others, and is thought to represent a compensatory mechanism for impaired lysosomal function.…”
Section: Discussionsupporting
confidence: 65%
“…Another major brain pathology feature in MLIV discovered by the proteomics data in the present and our previous studies was broad downregulation of the protein signature related to oligodendroglial cell lineage and myelination. 29 It is noteworthy that early intervention via ICV administration of AAV9-MCOLN1 in neonatal Mcoln1 −/− in our previous work resulted in an improvement of myelination in young adult Mcoln1 −/− mice at 2 months. However, CPP16-mediated MCOLN1 gene transfer in young adult symptomatic mice in the present study did not correct myelination, as shown by the lack of correction of myelination/oligodendrocyte signature in the brain proteomics dataset.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…An increased abundance of the lysosomal proteins and decreased levels of oligodendrocyte and myelin related proteins are molecular hallmarks in the brain of symptomatic Mcoln1 -/- mice (29). To assess if administration of CPP16 -MCOLN1 rescued brain pathology in Mcoln1 -/- mice, we next performed LC-MS/MS proteomics analysis using cortical tissues of 5-month-old female Mcoln1 -/- mice as well as wild-type control mice.…”
Section: Resultsmentioning
confidence: 99%
“…Protein extraction from cerebral cortex, TMT labeling and LC-MS/MS analysis was performed as previously described (29). Raw data were submited for analysis in Proteome Discoverer 3.0.1.23 (Thermo Scientific) software with Chimerys (MSAID, Germany).…”
Section: Methodsmentioning
confidence: 99%